Production of fuel grade bio oil and fuel gas from catalytic plastic pyrolysis : effect of temperature - Elizabeth, Hendroff (2015)
As the world faces increasing depletion of petroleum resources, and environmental concern escalates, many are scurrying to find alternative energy sources that are environmentally compatible as well as able to reduce the world’s dependency on petroleum resources. Plastic is a hydrocarbon that has the potential to be converted into an alternative fuel source. Thus, pyrolysis has become an increasingly explored alternative method to produce renewable energy from plastic waste. The application of specific catalyst improves the efficiency of the process and yield of the fuel gas and fuel grade bio oil produced. This research aims to synthesize and characterize Ni-Ce/Al2O3 as the catalyst and investigate the effect of temperature variation on the pyrolysis of Polyethylene (PE) in a catalytic reaction using a ratio of 1: 3 of catalyst: plastic to produce a high yield and quality fuel grade bio oil and fuel gas. The catalyst used in this study was synthesized to form an aqueous solution of alumina supported nickel with cerium as a promoter via the incipient wetness impregnation technique using a mass ratio of 75 wt. %, 20 wt. %, and 5 wt. % respectively and was tested in pyrolysis run at 500 oC to 800 oC. The catalyst was characterized using techniques such as Scanning Electron Microscopy (SEM), Brunauer Emmett Teller (BET) and Thermo Gravimetric Analysis (TGA). The fuel gas obtained were analysed via Gas-Chromatography-Thermal Conductivity Detector (GC-TCD) while the fuel grade bio oil produced were analysed via Gas Chromatography-Mass Spectrometry (GC-MS), Gas Chromatography-Flame Ionization Detector (GC-FID) and Fourier Transform Infrared Spectroscopy (FTIR). The findings suggest that a temperature of 700 oC with catalyst Ni-Ce/Al2O3 using a mass ratio of 20 wt. %, 5 wt. %, and 75 wt. % respectively was the most optimum temperature to run plastic pyrolysis and obtain high quality fuel gas and biofuel yield.